Development Strategy of Internet Interactive Video under the Background of 5G Converged Media and Wireless Communication. (9th November 2021) - Miao, Ruomu; Li, Juan; Gao, Jiayin
Abstract : At this stage, the promotion of 5G network has a positive basic value for the development of Internet interactive video. With the arrival of 5G era and the vigorous development of wireless communication technology, the trend of media convergence is more and more intense. The innovation of emerging technology and communication mode provides a strong support for the development of interactive video. With 5G technology as the background, Internet interactive video ushered in a blowout period of development. In recent years, video websites at home and abroad have launched interactive videos with their own characteristics. So, the imagination of integrated media evolved into the reality gradually. However, the excessively fast development speed concealed many existing shortcomings. There are still many constraints and deficiencies in the deep integration of each link of Internet interactive video. This paper discusses the development status of Internet interactive video and deeply analyzes the development characteristics of interactive video. In view of the existing problems, this paper puts forward development suggestions from the aspects of creating high-quality content and building "interactive video +" to help the better development of Internet interactive video.